Chlormequat chloride retards rat embryo growth in vitro. (August 2016) - Xiagedeer, Bayindala; Wu, Shuang; Liu, Yingjuan; Hao, Weidong
Abstract: Chlormequat chloride is the most widely used plant growth regulator in agriculture to promote sturdier growth of grain crops by avoidance of lodging. Therefore, human exposure to chlormequat chloride is very common, but its developmental toxicity has not been studied. Thus, we investigated the developmental toxicity of chlormequat chloride by applying rat whole embryo culture (WEC) model, limb bud micromass culture and 3T3 fibroblast cytotoxicity test. Chlormequat chloride at 150 μg/ml (0.93 mM) retarded the rat embryo growth without causing significant morphological malformations and at 500 μg/ml (3.1 mM) caused both retardation and morphological malformation of the embryos. However, the proliferation and differentiation of limb bud cells were not affected by chlormequat chloride at as high as up to 1000 μg/ml (6.2 mM) applied. This concentration of chlormequat chloride did not affect the cell viability as examined by 3T3 fibroblast cytotoxicity test either, suggesting that cellular toxicity may not play a role in chlormequat induced inhibition of rat embryo growth. Collectively, our results demonstrated that chlormequat chloride may affect embryo growth and development without inhibiting cell viability. Highlights: Chlormequat retards embryonic growth without causing malformations at 150 μg/ml. Chlormequat began to cause embryonic malformations at 500 μg/ml. Limb bud cell proliferation and differentiation could not be affected by chlormequat up to 1000 μg/ml. 3T3 cell proliferation could not be inhibited by chlormequat up to 1000 μg/ml.